Corruption in Nigeria’s Oil and Gas Industry: Measure and Extent - Yusuf Musbau; Yusuf Isah Maikudi; Abubakar Sadiq Suleiman (PanAfrican Journal of Governance and Development)
This study aims to develop a measure and ascertain the extent of corruption in Nigeria’s oil and gas industry. The opacity index approach to measuring corruption, as well as a conceptual framework that clarifies the concept of corruption and the context of a corruption analysis in Nigeria’s oil and gas industry, is used in developing the measure of corruption. The extent of corruption is measured by looking at the upstream, downstream, and aggregate sectors. The main findings of the study show that there is a persistence and enlargement in the scope of corruption in the oil and gas industry in Nigeria. The study also found that the oil and gas industry is highly vulnerable to large-scale corruption. The study concludes that corruption, in general and in the oil and gas industry, in particular, will thrive where there is opacity and unaccountability. It recommends, among other things, keeping accurate data on the activities of the industry, arrest, and prosecution of those involved in oil stealing, and entrenchment of institutional quality.